1996
DOI: 10.1007/bf01441630
|View full text |Cite
|
Sign up to set email alerts
|

Peer interactions of dysphoric adolescents

Abstract: The present study sought to extend our knowledge of dysphoric adolescents' dyadic peer interactions. Thirty female dyads (ages 13-17) were videotaped interacting during both a structured and an unstructured task. Fourteen of the dyads were each comprised of a dysphoric girl and a nondysphoric girl; the remaining dyads were comprised of two nondysphoric girls. Girls were considered dysphoric if they scored 10 or higher on the Beck Depression Inventory. Dysphoric subjects evaluated their performances more negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 20 publications
3
32
1
1
Order By: Relevance
“…Behaviors like these may lead to an increased likelihood of peer rejection or neglect. This possibility has been supported in several observational studies, which found that depressed children elicit negative reactions from other children during dyadic interactions (Baker, Milich, & Manolis, 1996;Connolly, Geller, Marton, & Kutcher, 1992;Rudolph et al, 1994).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Behaviors like these may lead to an increased likelihood of peer rejection or neglect. This possibility has been supported in several observational studies, which found that depressed children elicit negative reactions from other children during dyadic interactions (Baker, Milich, & Manolis, 1996;Connolly, Geller, Marton, & Kutcher, 1992;Rudolph et al, 1994).…”
mentioning
confidence: 73%
“…Behaviors like these may lead to an increased likelihood of peer rejection or neglect. This possibility has been supported in several observational studies, which found that depressed children elicit negative reactions from other children during dyadic interactions (Baker, Milich, & Manolis, 1996;Connolly, Geller, Marton, & Kutcher, 1992;Rudolph et al, 1994).However, such findings also may reflect, in part, the influence of co-occurring conduct problems on peer relationships. Indeed, in recent analyses from the Child Development Project, Lansford et al (2003) found that early peer rejection was not related to later depressive symptoms when children's concurrent levels of aggression were controlled, suggesting that the relation between peer rejection and later depressive symptoms may be due, in large part, to cooccurring externalizing problems.…”
mentioning
confidence: 83%
“…Indeed, most studies of peer influence on aggression have used adolescent samples. This is not surprising given the increasing importance during adolescence of the peer group in shaping a variety of individual outcomes including alcohol use (Curran, Stice, & Chassin, 1997), school adjustment (Berndt & Keefe, 1995), and emotional adjustment (Baker, Milich, & Manolis, 1996), in addition to antisocial behavior. However, it also is important to examine whether peer contagion effects seem to be operating in younger samples.…”
Section: Peer Contagion In Selected Prevention For Aggressionmentioning
confidence: 95%
“…Partial support for the hypothesis that depressed children's negative evaluations of their interactions tend to be based on a reality of lower quality interactions, in relation to nondepressed peers, was provided by Baker et al (1996). These researchers examined the post-game evaluations of dysphoric and nondysphoric target children and partners.…”
mentioning
confidence: 97%
“…Observers rated the interactions between depressed children and their partners as having significantly less conflict-negotiation competence (a composite of ratings of persistence in problem-solving efforts, positive assertiveness, positive conflict management, and general social competence), less adaptive affect-regulation (a composite of ratings of conflict exacerbation, positive affect, "outwardly directed" negative affect and "inwardly directed" negative affect), and lower dyadic quality (a composite of ratings of conflict, collaboration, problem-solving competence and mutuality). The third observational study (Baker, Milich, & Manolis, 1996) examined the interactions between dysphoric versus nondysphoric adolescent girls (defined by Beck Depression Inventory scores of ≥ 10 and ≤ 9, respectively), aged 13-17, with unfamiliar peers. Researchers found that while there were no differences between the observed emotional behavior of dysphoric versus nondysphoric adolescent girls during the interaction, the partners of dysphoric adolescent girls displayed more sadness and less positivity than did the partners of nondysphoric girls.…”
mentioning
confidence: 99%